Between Attraction and Evasion: Legal Factors Shaping FDI in Indonesia and Neighboring Countries - Adam, Richard C (UI Scholars Hub, 2025)
This article examines the internal and external factors that influence foreign direct investment (FDI) in Indonesia, focusing specifically on the legal framework as a key determinant. Internal factors—also referred to as pull factors—include the quality of Indonesia’s Foreign Investment Law, legal certainty, bureaucratic efficiency, and the availability of fiscal and non-fiscal incentives. Meanwhile, push factors represent external elements, such as the attractiveness of neighboring countries’ investment laws, regional economic integration, and global investment trends that encourage capital relocation. Using a normative juridical approach and qualitative analysis of secondary data, this study compares Indonesia’s regulatory environment with that of several Southeast Asian countries, particularly Vietnam, Malaysia, and Cambodia. The findings reveal that Indonesia’s legal infrastructure remains less agile and investor-oriented compared to these competitors. Regulatory complexity, inconsistent implementation, and a lack of legal predictability are identified as key weaknesses. To compete effectively and attract sustainable foreign investment, Indonesia must revamp its legal approach—prioritizing simplification, harmonization with international standards, and greater protection for investors. The article concludes that comprehensive legal reform is essential not only to enhance competitiveness but also to ensure that foreign investment contributes meaningfully to national development goals.